Fatal germination in barnyardgrass (Echinochloa crus-galli) - Zdenka MARTINKOVÁ; Alois HONĚK (Plant Protection Science, 2013)
Seeds of weeds buried by tillage may germinate at depths from which seedlings cannot establish. In barnyardgrass (Echinochloa crus-galli) we investigated how fatal germination was influenced by the depth and time of seed burial. The proportion of germinated seeds decreased with burial depth to 0-20% at ≥ 0.1 m depth which is fatal for seedling establishment. The percentage of fatal germination was greater for the seeds buried during the spring season than during autumn. Germination was influenced by seed pre-treatment, after ripening or stratification. Spring ploughing of non-dormant seeds below 0.1 m depth induces fatal germination, decreasing in this way seed bank of barnyardgrass.